Abiotic stress protection by ecologically abundant dimethylsulfoniopropionate and its natural and synthetic derivatives: insights from Bacillus subtilis. (17th December 2014) - Broy, Sebastian; Chen, Chiliang; Hoffmann, Tamara; Brock, Nelson L.; Nau‐Wagner, Gabriele; Jebbar, Mohamed; Smits, Sander H. J.; Dickschat, Jeroen S.; Bremer, Erhard
Summary Dimethylsulfoniopropionate (DMSP) is an abundant osmolyte and anti‐stress compound produced primarily in marine ecosystems. After its release into the environment, microorganisms can exploit DMSP as a source of sulfur and carbon, or accumulate it as an osmoprotectant. However, import systems for this ecophysiologically important compatible solute, and its stress‐protective properties for microorganisms that do not produce it are insufficiently understood. Here we address these questions using a well‐characterized set of Bacillus subtilis mutants to chemically profile the influence of DMSP import on stress resistance, the osmostress‐adaptive proline pool and on osmotically controlled gene expression. We included in this study the naturally occurring selenium analogue of DMSP, dimethylseleniopropionate (DMSeP), as well as a set of synthetic DMSP derivatives. We found that DMSP is not a nutrient for B. subtilis, but it serves as an excellent stress protectant against challenges conferred by sustained high salinity or lasting extremes in both low and high growth temperatures. DMSeP and synthetic DMSP derivatives retain part of these stress protective attributes, but DMSP is clearly the more effective stress protectant. We identified the promiscuous and widely distributed ABC transporter OpuC as a high‐affinity uptake system not only for DMSP, but also for its natural and synthetic derivatives.